Fashion designers’ autobiographies as tool for historical research (ModaPalavra e-periódico, 2015)
Fashion designers represent a constitutive part of modern western fashion and are among the most intriguing and controversial of its figures. Fashion is a system centered on design, but tends to exclude the designer from theoretical and historical discourse. In other fields of cultural production, artists and architects have provided a key focus –by means of their writings –on major themes in their fields, thus contributing to developing them into historiography and literature. In the case of fashion, on the contrary, the textual material that fashion designers produce is considered as promotional to the designers themselves, their collections, and their brand. This interpretation is accepted by the fashion industry as well as by fashion studies, which acknowledge the severely limited contribution that designers themselves make to historiography and criticism. The paper intends discuss the historical and current role of designer-based explanations in the field of fashion. Taking into consideration fashion designers’ writings from 20th and 21th centuries, the paper explores fashion designers’ autobiographical accounts of their entry into the world of fashion, with particular attention paid to education and apprenticeship. It also provides insight into the difficulties that designers experience in managing their public image.
Keywords: fashion designer; autobiography; authorship; self-expression; fashion history